Android-Based SIGAP Application to Increase the Effectiveness of Student Management - Ni Made Astiti Byantari; Yari Dwikurnaningsih; Marinu Waruwu (Jurnal Edutech Undiksha, 2023)
There needs to be better relationships between parents and schools to improve student discipline and increase achievement. Collaboration between parents and teachers should improve student discipline and achievement. This research aims to create an Android-based SIGAP application to increase the effectiveness of student management. This research is development research using the Borg and Gall model. The research subjects were the Principal, Deputy Principal for Student Affairs, teachers, students, and parents. Data collection techniques use interviews, documentation studies, and questionnaires. The data analysis technique uses quantitative descriptive analysis for quantitative data and the Miles and Huberman model for qualitative data. The resulting product is an Android-based SIGAP application, a book containing a description of the SIGAP application, a guide for teachers, a guide for students, and a guide for parents. Product Validation Results ICT experts validated the SIGAP Application with results of 89% and management experts with 96% or a very good title. Trials are given to teachers, students, and parents. The test results for teachers were 93%, for students 92%, and for parents 85%. The conclusion is that the SIGAP application is effective to use.